2018
DOI: 10.1002/wps.20544
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of the clinical utility of a prolonged grief disorder diagnosis

Abstract: The authors alone are responsible for the views expressed in this letter and they do not necessarily represent the decisions, policy or views of the World Health Organization. The letter is based in part upon work from Action CA16207 "European Network for Problematic Usage of Internet", supported by the European Cooperation in Science and Technology (COST).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 9 publications
0
15
0
1
Order By: Relevance
“…ICD-11 included 'prolonged grief disorder (PGD)' (WHO, 2018). Provided that these labels are carefully used, they foster the identification of people suffering severely following loss and enable the delivery of effective treatment (Lichtenthal et al, 2018) Over the past years, the European Journal of Psychotraumatology has published key papers on traumatic loss informing both scientific and clinical practice (see Olff, 2018). Several papers in this journal have set research agendas.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…ICD-11 included 'prolonged grief disorder (PGD)' (WHO, 2018). Provided that these labels are carefully used, they foster the identification of people suffering severely following loss and enable the delivery of effective treatment (Lichtenthal et al, 2018) Over the past years, the European Journal of Psychotraumatology has published key papers on traumatic loss informing both scientific and clinical practice (see Olff, 2018). Several papers in this journal have set research agendas.…”
mentioning
confidence: 99%
“…ICD-11 included ‘prolonged grief disorder (PGD)’ (WHO, 2018 ). Provided that these labels are carefully used, they foster the identification of people suffering severely following loss and enable the delivery of effective treatment (Lichtenthal et al, 2018 )…”
mentioning
confidence: 99%
“…The second priority concerned distinguishing grief from mental health issues (e.g., depression, PTSD, anxiety, identity disorder and trauma). A recent randomized, controlled trial tested the utility of written information on practitioners' ability to differentially diagnose PGD from normative grief, PTSD, and Major Depressive Disorder (Lichtenthal et al, 2018). The study showed that practitioners can be trained to distinguish between these disorders in order to diagnose PGD accurately, which is important for practitioners to be able to provide appropriate interventions.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical utility of a classification system is distinct from its validity, although these two constructs are highly correlated, since a diagnosis cannot have a good value in terms of clinical utility but lacking any clinical validity [17,29,42]. Ideally, a classification system with a satisfying level of clinical utility should allow clinicians to identify the best diagnostic category for each patient and should provide useful information on disease's treatment and management [22,28,40].…”
mentioning
confidence: 99%